Analysis of Factors Influencing User Acceptance and Satisfaction with Google Classroom in Hybrid Learning using an Integrated EUCS and TAM Approach - Iklas Nurul Islam; Wire Bagye; Lalu Mutawalli (SISTEMASI, 2026)
The use of Google Classroom in hybrid learning needs to be evaluated to determine the extent to which users perceive the system as useful and satisfactory for their learning activities. This study examines user acceptance and satisfaction with Google Classroom in hybrid learning by integrating the Technology Acceptance Model (TAM) and the End-User Computing Satisfaction (EUCS) model. A quantitative approach was employed involving 155 respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the support of SmartPLS software. The study investigates how various EUCS dimensions, including Format, Timeliness, Content, and Accuracy, are associated with TAM constructs, namely Perceived Ease of Use, Perceived Usefulness, User Satisfaction, and Behavioral Intention. The results show that eight of the ten hypotheses were supported, while the remaining two were not supported. Format has a significant effect on Perceived Ease of Use. In addition, Timeliness and Content significantly affect Perceived Usefulness. Perceived Ease of Use and Perceived Usefulness significantly affect User Satisfaction, while Perceived Usefulness and User Satisfaction significantly affect Behavioral Intention. In contrast, Accuracy does not significantly affect Perceived Usefulness, and Perceived Ease of Use does not have a significant effect on Behavioral Intention. These findings indicate that Perceived Usefulness and User Satisfaction are important factors in driving users’ Behavioral Intention to use Google Classroom in hybrid learning.